A comparative study on the efficacy of commercially available denture cleanser and detergent in eliminating candida albicans colonies on acrylic resin - Bautista, Ermina Angela
This study was geared towards identifying a more economical and practical alternative for commercially available denture soak. The main objective was to determine if the efficacy of the detergent solution was comparable with the denture cleanser in eliminating Candida albicans colonies on acrylic resin. Specifically, the researchers would like to determine if the detergent solution can effectively eliminate Candida albicans colonies on the acrylic resin surface when used as chemical soak and at what concentration and immersion period it was most effective. The results obtained regarding efficacy of detergent solution in eliminating Candida albicans colonies on acrylic resin were compared with that of the denture cleansers. Experimental research method was used accompanied by simple random technique as sampling method. Using the methodology in the study by Foronda (2000) with some modifications, the following results were obtained: (1) the detergent solution was not effective in eliminating Candida albicans colonies on acrylic resin however the number of colony forming units was reduced (2) the concentration does not greatly affect the efficacy of Candida albicans reduction (3) as the immersion time is increased there is also a greater reduction in the number of colonies left after treatment; (4) the detergent solution has greater percent (%) reduction than the denture cleanser solution. Therefore. we accept our null hypothesis that the detergent solution is not effective in eliminating Candida albicans colonies on acrylic resin.